Effectiveness of the Community Early Warning Forum Program in the Sub-Department of National Unity and Political Affairs in Tanjung Priok District - Ahmad Taohid; Muhammad Ridhwan (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
The Community Early Warning Forum (Forum Kewaspadaan Dini Masyarakat/FKDM) is a participatory platform for community participation in identifying and preventing potential threats, challenges, obstacles and disturbances (ATHG) that could impact public security and social order. This research aims to analyse the performance of FKDM program conducted by Sub-Department of National Unity and Political Affairs (Subankesbangpol) of North Jakarta Administrative City especially in Tanjung Priok District. A descriptive qualitative approach was utilized using interviews, observations and documentation as data collection techniques. Informants were purposively selected. The results show that the cross-sectoral cooperation of the State Intelligence Agency (BIN), the Indonesian National Armed Forces (TNI), the Indonesian National Police (Polri), the Attorney General’s Office, and intelligence units from ministries and non-ministerial government agencies strongly supports the success of the FKDM program. FKDM in Tanjung Priok has track various programs, including a campaign to raise the awareness of community security, neighbourhood watch and night patrol activities, education on disaster management, anti-drug campaigns, and family-strengthening programs. These initiatives have resulted in increased public awareness, reduced crime rates and better coordination of local security. However, there are still challenges in terms of resource optimization, capacity building of members and long-term sustainability of the programs. Therefore, the study recommends that training programs should be improved, the utilization of information technology should be expanded and collaboration among stakeholders should be strengthened to enhance FKDM’s role in preserving the security of the community and public order.